Dano foliar de percevejo-de-renda (Vatiga spp. Drake) na cultura da mandioca, escala de nota e prospecção de parasitoides de ovo - Uemura-Lima, Daliana Hisako (2017)
Native the Amazon, manioc (Manihot esculenta Crantz) can be consider one of the most important crops for its contribution to human consumption, besides being considered the option to combat hunger in the world.Their cultivation is subject to the attack of diverse insects and mites. Some of these classified as major pests and can cause severe damage to the crop and result in yield losses. Historically, it did not usually present major problems with pests, but with the increase of its cultivation in monoculture and the incorrect handling of the crop, the lacebug (Vatiga spp.) has been gaining attention in recent years. This insect is locate on the abaxial side of the leaves of the middle third of the plant, causing a reduction in the photosynthetic rate and lower leaf fall. The objective of this research was to develop new research related to the pest, aiming at a future implantation of integrated pest management, assessing the potential of leaf damage and prospecting natural enemies.The leaf damage aspects were evaluated in the Fécula Branca variety, with different population densities for up to 30 days of insect stay in the leaves. Evaluating the use of the scale of note to quantify the damage of the pest in the leaves, to investigate changes in the gas exchanges and biochemical responses of the leaf.The indices SPAD, A, gs, Ci, E, EUA, Fc, and activities by polyphenoloxidase, peroxidase, chlorophyll, carotenoid, anthocyanin and reducing sugar contents were evaluated. To verify the occurrence of natural enemies of Vatiga spp. eggs collected in cassava plantations of the variety Baianinha and Cascuda. Identifying the species of parasitoids that occur associated with eggs of this pest, raising their fluctuation throughout the period of occurrence of the pest and establishing the rate of parasitism. The experiments carried out in the culture in two crop cycles of manioc. It observed that the scale of note established was adequate to assess the damage of the lacebug. The values of SPAD and A rate were elevated while the population of the pest and its residence time of the experiment increased. Chlorophyll pigments influenced by the attack of the insects, reducing their values as peroxidase and sugars increased in the measurements made. There was a difference in the response rate of the first and second cycle cassava plant. Two species of parasites of the Mymaridae family, Anagrus virginiae Puttler and Triapitsyn (2006) and Erythmelus tingitiphagus Soares (1941), parasitizing the eggs of V. manihotae Drake (1922) and V. illudens Drake (1922) were found. The species A. virginiae had a higher parasitism potential, especially in the first-cycle Baianinha variety. The first-cycle cassava plants showed a higher number of oviposition of the bedbug than the second cycle. There was a positive correlation for the number of pest eggs with temperature and negative for moisture and precipitation.